Inflammatory Cytokines—The Link between Coronavirus Disease and Abortion: A Case‐Control Study - Samar Muayad Alfadhel; Niran Ali Thamer (Medical Journal of Babylon)
Background: Coronavirus disease (COVID-19) infection and the risk of abortion have become a major concern for pregnant women worldwide. Whereas research studies have not yet determined the exact risk of abortion due to COVID-19 infection, the virus could increase the risk of pregnancy complications through inflammatory cytokines and immune response. Objective: The study highlights prognostic markers for pregnancy complications during COVID-19 infections by testing interleukin-6 (IL-6), interleukin-18 (IL-18), tumor necrosis factors-α (TNF-α), and interferon-γ (INF-γ) in the serum of pregnant women with and without COVID-19. Materials and Methods: A case‐control study consists of 100 cases; included are 50 COVID-19 pregnant women matched with 50 non-COVID-19 pregnant women, with both groups free from any abortion risk factors. The study measured serum IL-6, IL-18, TNF-α and INF-γ tests to predict cases with severe infection and those at high risk for fetal loss. Results: The statistical analysis showed a significant relationship between elevated immunological markers levels and the severity of COVID-19 and pregnancy complication P value (0.001, 0.005, 0.001, and 0.001 for IL-6, IL-18, TNF-α, and INF-γ, respectively). Furthermore, the odd ratio explains that elevated immunological markers increased the risk of baby loss; through COVID-19 infection. In addition, receiver operating characteristic curve analysis verified these accuracies; the excellent test referred to IL-6, followed by IL-18 and INF-γ very good tests, then TNF-α as a medium test to predict the risk of pregnancy complication. Conclusion: These results concluded that monitoring these immunological markers’ levels could help predict COVID-19 infection in the severe stage and the risk of pregnancy complications in COVID-19-positive women.